2004
DOI: 10.1084/jem.20040168
|View full text |Cite
|
Sign up to set email alerts
|

Short-lived Plasmablasts and Long-lived Plasma Cells Contribute to Chronic Humoral Autoimmunity in NZB/W Mice

Abstract: The current view holds that chronic autoimmune diseases are driven by the continuous activation of autoreactive B and T lymphocytes. However, despite the use of potent immunosuppressive drugs designed to interfere with this activation the production of autoantibodies often persists and contributes to progression of the immunopathology. In the present study, we analyzed the life span of (auto)antibody-secreting cells in the spleens of NZB × NZW F1 (NZB/W) mice, a murine model of systemic lupus erythematosus. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
386
2
12

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 405 publications
(408 citation statements)
references
References 36 publications
8
386
2
12
Order By: Relevance
“…2 As both short-and long-lived Ig-secreting cells are involved in the pathology of SLE, signaling through both TACI and BCMA might contribute to the disease. 49 We have shown that TACI respond to oligomerized ligands, and it will be of interest to determine whether BAFF 60-mer may be produced in excess in these pathologies and whether the specific targeting of BAFF 60-mer may represent an alternative treatment for these autoimmune disorders.…”
Section: Discussionmentioning
confidence: 99%
“…2 As both short-and long-lived Ig-secreting cells are involved in the pathology of SLE, signaling through both TACI and BCMA might contribute to the disease. 49 We have shown that TACI respond to oligomerized ligands, and it will be of interest to determine whether BAFF 60-mer may be produced in excess in these pathologies and whether the specific targeting of BAFF 60-mer may represent an alternative treatment for these autoimmune disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Both SLE patients and lupus-prone mice have alterations in their B-cell subsets, such as an increased proportion of plasmablasts and/or plasma cells, GCs, etc., [39][40][41][42][43] which reflects the disturbed differentiation of B cells in SLE patients and lupus-prone mice. In the present study, we found that compared with wild-type mice, CD138 1 plasmablasts/plasma cells and B220 1 GL-7 1 GC B cells are increased in MRL/lpr mice and are CD180-negative.…”
Section: Discussionmentioning
confidence: 99%
“…After 3-5 days of culture, [ 3 H]thymidine was added to the culture for additional 18 h. [ 3 H]Thymidine uptake was measured using a liquid scintillation counter. In some experiments, stimulated and control cultures were stained after various intervals with anti-CD19 PerCP-Cy5.5 (1D3) and allophycocyanin-conjugated anti-CD138 (281-2) to visualize plasma cells, which were identified as CD19 low/-CD138 + cells [42].…”
Section: B Cell Proliferation and Differentiationmentioning
confidence: 99%